Effect of Zoocin A on Growth of the Biofilm Producing Cariogenic Oral Bacteria - Zamanian, Zohreh; Pour, Nahid Arian (UI Scholars Hub, 2017)
Zoocin A has a potential antibacterial properties and its use as an anti-cariogenic agent needs to be explored Objective: Dental caries is an infectious disease, caused mainly by mutans streptococci (MS). The aim of the present study is to evaluate the antimicrobial effect of zoocin A on the biofilm producing cariogenic oral bacteria compared with antibiotics. Methods: The samples were collected from dental caries and plaques of 130 cases referring to eight government dental clinics of Hamedan- Iran for treatment. The isolated bacteria were identified on the basis of morphological, biochemical and molecular methods. The antimicrobial effects of the zoocin A and antibiotics were compared. Results: Zoocin A showed varying degrees of inhibition on the most common oral biofilm producing bacteria we isolated which were identified as S. mutans, S. mitis, S. sanguinis, S. gordonii, Lactobacillus gasseri, and Granulicatella adiacens by PCR using16S rRNA gene sequence. Minimum inhibitory concentration (MIC) of 2.2 mg-l and 3.2 mg-l was observed against S. mutans and S. gordonii respectively. Conclusion: In Hamedan, S.mitis and S. mutans are dominant species in decayed teeth of cases referring to government dental clinics. Isolated bacteria showed varying sensitivity to different antibiotics. Zoocin A inhibited the growth of some Streptococcal species like S. mutans and S. gordonii. Antimicrobial property of Zoocin A against cariogenic agents collected from high risk caries patients is equal to antibiotics tested in this study.